Purine derivatives with antituberculosis activity. (June 2018) - Gruzdev, Dmitry A.; Musiyak, Vera V.; Levit, Galina L.; Krasnov, Victor P.; Charushin, Valery N.
Abstract : The review summarizes the data published over the last 10 – 15 years concerning the key groups of purine derivatives with antituberculosis activity. The structures of purines containing heteroatoms (S, O, N), fragments of heterocycles, amino acids and peptides, in the 6-position, as well as of purine nucleosides are presented. The possible targets for the action of such compounds and structure – activity relationship are discussed. Particular attention is paid to the most active compounds, which are of considerable interest as a basis for the development of efficient antituberculosis drugs. The bibliography includes 99 references.